Psychology and school failure/complaint: an analysis of scientific production (Research, Society and Development, 2021)
This research investigated in the scientific productions in the area which factors are attributed to school failure/complaints, analyze the psychologist's actions and identify possible alternative interventions to the traditional model of blaming. This is a literature review with descriptors "school failure" and "school complaint" on the Scielo and Pepsic platforms, published in the time series between 2009 and 2018. We found a total of 20 articles, 75% of which were published in the last five years. The authors searched for the conceptions of school failure/complaints that the authors pointed out, and which factors attributed to the production of school complaints, and the role of the psychologist in this demand, and if any type of intervention aimed at the area was described. In 70% of the researches, the authors understand failure as a multifaceted phenomenon and that school failure is mostly produced by relationships inside and outside the school environment. Regarding the practice of psychology, 95% of the research highlighted the need for re-signification of the school complaint in the institutional environment, since students with learning difficulties or behaviors that are outside the norm are considered to have a biological disease, 60% of the researches they did not effectively show how to intervene in school failure/complaints and 25% indicated the need for alternative interventions in relation to school complaints. With this research, we highlight there are recent productions in the area of ​​school/educational psychology and that this demonstrates that it needs further deepening and scientific studies that describe and discuss the concrete practice of the psychologist.